Epidemiological Impact of GII.17 Human Noroviruses Associated With Attachment to Enterocytes - Estienney, Marie; Tarris, Georges; Abou-Hamad, Nicole; Rouleau, Alain; Boireau, Wilfrid; Chassagnon, Rémi; Ayouni, Siwar; Daval-Frerot, Philippe; Martin, Laurent; Bouyer, Frédéric; Le Pendu, Jacques; de Rougemont, Alexis; et al. (Frontiers in Microbiology, 2022)
For the last 30 years, molecular surveys have shown that human norovirus (HuNoV), predominantly the GII.4 genotype, is one of the main causative agents of gastroenteritis. However, epidemiological surveys have revealed the worldwide emergence of GII.17 HuNoVs. Genetic analysis confirmed that GII.17 strains are distributed into three variants (i.e. Kawasaki 308, Kawasaki 323 and CS-E1). Here, virus-like particles (VLPs) were baculovirus-expressed from these variants to study putative interactions with HBGA. Qualitative analysis of the HBGA binding profile of each variant showed that the most recent and predominant GII.17 variant, Kawasaki 308, possesses a larger binding spectrum. The retrospective study of GII.17 strains documented before the emergence of the dominant Kawasaki 308 variant showed that the emergence of a new GII.17 variant could be related to an increased binding capacity towards HBGA. The use of duodenal histological sections confirmed that recognition of enterocytes involved HBGA for the three GII.17 variants. Finally, we observed that the relative affinity of recent GII.17 VLPs for HBGA remains lower than that of the GII.4-2012 variant. These observations suggest a model whereby a combination of virological factors, such as polymerase fidelity and increased affinity for HBGA, and immunological factors was responsible for the incomplete and non-persistent replacement of GII.4 by new GII.17 variants.